2013
DOI: 10.1021/jf304882k
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum, a Healthy and Gluten-free Food for Celiac Patients As Demonstrated by Genome, Biochemical, and Immunochemical Analyses

Abstract: Wheat (Triticum spp. L.), rye (Secale cereal L.), and barley (Hordeum vulgare L.) seeds contain peptides toxic to celiac patients. Maize (Zea mays L.) and rice (Oryza sativa L.) are distant relatives of wheat as well as sorghum (Sorghum bicolor (L.) Moench) and are known to be safe for celiacs. Both immunochemical studies and in vitro and in vivo challenge of wheat-free sorghum food products support this conclusion, although molecular evidence is missing. The goal of the present study was to provide biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 36 publications
1
58
0
6
Order By: Relevance
“…In sub-Saharan Africa and Southeast Asia, sorghum is grown primarily as a food crop by small-scale subsistence farmers in some of the world's most fragile agroecosystems. In other parts of the world, sorghum is principally grown as an animal feed, although there is a growing interest in recent years to use it in food products driven by its potential human health benefits (Awika and Rooney, 2004;Lemlioglu-Austin, 2014;Dahlberg et al, 2011;Stefoska-Needham et al, 2015) and as a celiac-safe grain (Ciacci et al, 2007;Pontieri et al, 2013). Over the last decade, sorghum has found new use as feedstock for biofuel production (Dahlberg et al, 2011;Ratnavathi et al, 2011), with nearly one-third of grain sorghum going to the ethanol industry.…”
Section: Review and Interpretationmentioning
confidence: 99%
“…In sub-Saharan Africa and Southeast Asia, sorghum is grown primarily as a food crop by small-scale subsistence farmers in some of the world's most fragile agroecosystems. In other parts of the world, sorghum is principally grown as an animal feed, although there is a growing interest in recent years to use it in food products driven by its potential human health benefits (Awika and Rooney, 2004;Lemlioglu-Austin, 2014;Dahlberg et al, 2011;Stefoska-Needham et al, 2015) and as a celiac-safe grain (Ciacci et al, 2007;Pontieri et al, 2013). Over the last decade, sorghum has found new use as feedstock for biofuel production (Dahlberg et al, 2011;Ratnavathi et al, 2011), with nearly one-third of grain sorghum going to the ethanol industry.…”
Section: Review and Interpretationmentioning
confidence: 99%
“…In the United States, sorghum is mostly grown for animal feed and as a biofuel feedstock. However, since sorghum has important potential human health benefits in the prevention of chronic diseases (Stefoska-Needham, Beck, Johnson, & Tapsell, 2015) and with its use as a gluten-free food (Ciacci et al, 2007;Pontieri et al, 2013), sorghum use in the food industry is also increasing in America.…”
mentioning
confidence: 99%
“…The analysis of aqueous/alcohol-soluble prolamins (kafirins) from different sorghum varieties provides molecular evidence for the absence of toxic gliadin-like peptides in sorghum (Pontieri et al, 2013). A similar study carried out with amaranth revealed that all of the amaranth samples studied showed similar binding affinities for both specific anti-gliadin antibodies and human IgAs, and the molecular characterisation of amaranth proteins suggests that it is safe for coeliacs to consume (Ballabio et al, 2011).…”
Section: Cereals Reported To Be Gluten Freementioning
confidence: 99%